2016
DOI: 10.1002/ece3.1929
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and phylogeography of the Gentoo Penguin (Pygoscelis papua) across the Scotia Arc

Abstract: Climate change, fisheries' pressure on penguin prey, and direct human disturbance of wildlife have all been implicated in causing large shifts in the abundance and distribution of penguins in the Southern Ocean. Without mark‐recapture studies, understanding how colonies form and, by extension, how ranges shift is challenging. Genetic studies, particularly focused on newly established colonies, provide a snapshot of colonization and can reveal the extent to which shifts in abundance and occupancy result from ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 107 publications
(206 reference statements)
4
40
1
Order By: Relevance
“…The currently recognized taxonomy of gentoo penguins is for two subspecies, the northern ( Pygoscelis papua papua ) distributed north of 60°S, and the southern ( Pygoscelis papua ellsworthii ) distributed on the Antarctic Peninsula and maritime Antarctic islands south of 60°S (Clements et al., ; Forster, ; Murphy, ). Our data support the existing classification of a northern gentoo subspecies; however, contrary to current taxonomic limits (Clements et al., ), we found that South Georgian gentoos are more closely related to the southern subspecies than the northern, a conclusion that is supported by previous studies of morphology (de Dinechin et al., ), mitochondrial DNA (Clucas et al., ) and microsatellites (Levy et al., ). We recommend formal taxonomic revision of the boundary between northern and southern gentoo penguins to reflect this.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The currently recognized taxonomy of gentoo penguins is for two subspecies, the northern ( Pygoscelis papua papua ) distributed north of 60°S, and the southern ( Pygoscelis papua ellsworthii ) distributed on the Antarctic Peninsula and maritime Antarctic islands south of 60°S (Clements et al., ; Forster, ; Murphy, ). Our data support the existing classification of a northern gentoo subspecies; however, contrary to current taxonomic limits (Clements et al., ), we found that South Georgian gentoos are more closely related to the southern subspecies than the northern, a conclusion that is supported by previous studies of morphology (de Dinechin et al., ), mitochondrial DNA (Clucas et al., ) and microsatellites (Levy et al., ). We recommend formal taxonomic revision of the boundary between northern and southern gentoo penguins to reflect this.…”
Section: Discussionsupporting
confidence: 89%
“…0.60 Ma (Supporting information Table ). It should be noted that our estimates of divergence time differ markedly from those based on mitochondrial data (Clucas et al., ; Levy et al., ), most likely because mitochondrial data alone were unable to resolve the topology completely, resulting in more recent coalescent events. The same pattern of relatedness was evident from our DAPC and PCA analyses (Figure e, Supporting information S5e).…”
Section: Resultscontrasting
confidence: 62%
“…The present study is the most comprehensive analysis of geographic variation in Gentoo Penguin ecstatic calls to date and provides a finer geographic scale at which to examine vocal differentiation. Genetic data from de Dinechin et al (2012) and Levy et al (2016) show the Falkland Islands populations as divergent clades from the Antarctic Peninsula, South Georgia, and the South Orkney Islands. The polar front provides a strong ecological barrier that is likely to maintain this separation and may have led to drift of ecstatic display calls over a long period of geographic isolation.…”
Section: Discussionmentioning
confidence: 99%
“…In the Atlantic region of their range, the polar front creates a strong ecological boundary between populations in Argentina and the Falkland Islands and those in South Georgia, the South Sandwich Islands, the South Orkney Islands, and the Antarctic Peninsula (Figure 1). This geographic and ecological isolation, combined with high mate and colony fidelity (Lynch 2013), results in strong population genetic structure between regions (Levy et al 2016). There are currently 2 described subspecies, originally based heavily on morphology (Stonehouse 1970) and now confirmed with genetics (de Dinechin et al 2012, Levy et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation